Effect of storage time on the physiological characteristics and vegetative regeneration of desiccation‐tolerant mosses on the Loess Plateau, China. (12th January 2020) - Guo, Yuewei; Zhao, Yunge; Downing, Alison J.
Abstract : The artificial cultivation of moss biocrusts can accelerate the recovery of degraded arid lands and is closely related to moss productivity. Understanding the properties of inoculation materials on the regenerative capacity of mosses, in particular the effect of time limits on storage, has the potential to benefit the cultivation of artificial moss biocrusts. We investigated the vegetative regeneration and physiological characteristics of three desiccation‐tolerant mosses ( Barbula unguiculata, Didymodon vinealis, and Didymodon tectorum ) upon rehydration after periods of desiccation storage for 40, 89, 127, and 197 days. Regenerative capacity, represented by gametophyte vigor index, decreased with increased storage time. The greatest change in vegetative regeneration among storage times was observed in B. unguiculata, where the gametophyte vigor index decreased by 95.74% after 197 days of storage. Over the same period, there were smaller decreases in gametophyte vigor index of D. vinealis and D. tectorum of 42.17% and 13.30%, respectively. Malondialdehyde and soluble sugar increased with longer periods of storage time, while soluble protein content first increased, then decreased. Oxidation levels are important factors influencing the recovery of desiccation‐tolerant mosses. All three moss species regenerated after 197 days of storage, but regenerative capacity is dependent on species. For land managers, biocrust restoration can be facilitated by careful screening of suitable moss species, based on their capacity to regenerate new growth after extended periods of storage and selection of species based on variations in physiological characteristics.